A meta regression analysis of quality of life correlates in adults with ASD. (July 2019) - Kim, So Yoon; Bottema-Beutel, Kristen
Highlights: QoL was not significantly correlated with age, IQ, or autism severity. QoL was significantly and positively associated with social functioning. Neither percentage of male participants nor chronological age moderated effect sizes. Abstract: Background: In this meta-regression analysis, we investigated Pearson's r correlations between Quality of Life (QoL) and several putative correlates, including (a) age, (b) intellectual quotient (IQ), (c) autism severity, and (d) social functioning (SF). Method: Robust variance estimation was used to synthesize the effect sizes from published and unpublished studies/datasets. One hundred sixty five effect sizes (extracted from 17 studies/datasets) comprising a total of 1721 participants with ASD (mean age = 35.64 years; mean percent male = 62.24%) were retrieved. Results: Summary effect sizes derived from unconditional meta-regressions for the association between QoL and age, IQ, and autism severity were close to zero and statistically insignificant. In contrast, the summary effect size for the association between QoL and social functioning was statistically significant and moderately sized. Conclusion: Of the correlates we examined, only social functioning appears to bear significant summary-level associations with QoL. Improvements in social functioning may enhance QoL in adults with ASD. Alternatively, interventions aimed at neurotypical populations that promote ASD acceptance may lead to increased QoL that is not dependent on social functioning. Factors other than normative adult outcomes that may influence adult QoL should be explored.